Current Status of Chikungunya in India - Sunil, Sujatha (Frontiers in Microbiology, 2021)
Chikungunya fever (CHIKF) is an arbovirus disease caused by chikungunya virus (CHIKV), an alphavirus of Togaviridae family. Transmission follows a human-mosquito-human cycle starting with a mosquito bite. Subsequently, symptoms develop after 2-6 days of incubation, including high fever and severe arthralgia. The disease is self-limiting and usually resolve within two weeks. However, chronic disease can last up to several years with persistent polyarthralgia. Overlapping symptoms and common vector with dengue and malaria present many challenges for the diagnosis and treatment of this disease. CHIKF was reported in India in 1963 for the first time. After a period of quiescence lasting up to 32 years, CHIKV re-emerged in India in 2005. Currently, every part of the country has become endemic for the disease with outbreaks resulting in huge economic and productivity losses. Several mutations have been identified in circulating strains of the virus resulting in better adaptations or increased fitness in the vector(s), effective transmission, and disease severity. CHIKV evolution has been a significant driver of epidemics in India, hence, the need to focus on proper surveillance, and implementation of prevention and control measures in the country. Presently, there are no licensed vaccines or antivirals available; however, India has initiated several efforts in this direction including traditional medicines. In this review, we present the current status of CHIKF in India.